Critical Infrastructure Protection in the Republic of Serbia – Current Status and Opportunities for further Development and Improvement - Radivojević, Nenad; Marković, Jana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
Critical infrastructure is considered the basis of the functioning of the state and society, and is one of the key factors of security and economic development, as well as the health and social well-being of citizens. Its protection is gaining particular importance in the era of globalization and with increasing exposure to various risks – from natural disasters to terrorist and cyber attacks. The Republic of Serbia, in accordance with modern security trends and the process of rapprochement with the European Union, has taken a number of specific normative and institutional steps to regulate and improve the critical infrastructure protection system. One of these steps is the adoption of the first systemic law regulating this area in 2018 – the Law on Critical Infrastructure.The aim of this paper is to present the current model of critical infrastructure protection through an analysis of the strategic and legal framework of the Republic of Serbia. Special emphasis is placed on the analysis of the Law on Critical Infrastructure, its implementation in the seven-year period since its adoption, as well as the identification of advantages, shortcomings and challenges in its implementation. The paper points to the importance of cooperation between the public and private sectors, as well as the need to strengthen institutional capacities, coordination and resilience of the critical infrastructure system. Based on the analysis conducted, the authors propose possible directions for further development and improvement of both the regulatory and practical framework for the protection of critical infrastructure in the Republic of Serbia.
Keywords: critical infrastructure; , critical infrastructure protection; Law on Critical Infrastructure; national security